New Graphidaceae from northern Argentina - Ferraro, Lidia Itati; Lücking, Robert; Aptroot, André; Cáceres, Marcela Eugenia Da Silva (Phytotaxa, 2014)
Six new species of Graphidaceae are described from northern Argentina: Graphis tetracarbonisata, with apical carbonization and additional patchy carbonization at the basis of the labiae, ascomata of the anguilliradians-morph, ascospores submuriform, 15–19-septate and with a few longitudinal septa, 73–87 × 13–16 μm, and thallus containing substances of the stictic acid complex; Leucodecton pustulatum, with gnarled confluent pustules and substances of the stictic acid complex; Ocellularia marmorata, which is close to O. auberianoides but with maculate thallus, blackened columella and without secondary chemistry; O. misionensis, differing from O. obturascens in the more complex, carbonized columella and lack of secondary substances; O. papillifera, with a thick thallus covered with papillae resembling pseudocyphellae and with large, columnar crystal clusters; and Rhabdodiscus argentinensis, similar to R. auberianus but with erumpent ascomata, smaller, consistently 3-septate ascospores, and stictic acid in addition to psoromic acid.